Analyzing the Effectiveness of Learning Motivation in Enhancing Communicative Competence among Learners of Arabic as a Foreign Language in Brunei Darussalam - Achmad Yani; Siti Sara Binti Haji Ahmad; Rafidah Binti Abdullah; siti shalihah; Anis Malik Thoha (Jurnal Al-Maqoyis, 2025)
This study aims to evaluate the effectiveness of the Communicative Arabic course in enhancing students’ learning motivation and engagement in educational activities. Employing a descriptive-evaluative quantitative methodology, the research integrates statistical measurement with a nuanced pedagogical analysis of the psychological and behavioral dynamics associated with language acquisition. A purposive sample of twelve first-year students from the Faculty of Usuluddin at Sultan Sharif Ali Islamic University (UNISSA) was selected, as they represent a key demographic actively involved in learning Arabic as a foreign language. The study utilized a structured, closed-ended questionnaire developed in alignment with well-established theories in educational psychology, including Self-Determination Theory (Deci & Ryan, 1985), the Theory of Planned Behavior (Ajzen, 2000), and Self-Regulated Learning Theory (Zimmerman, 2002). The instrument’s validity was ensured through expert review, and its reliability was confirmed with a high Cronbach’s Alpha coefficient of 0.89, indicating strong internal consistency and statistical significance. The findings reveal that a significant majority of participants (88.3%) demonstrated high intrinsic motivation toward learning communicative Arabic. Additionally, 93.3% reported positive emotional attitudes toward the course, exhibiting the same high level of active participation in classroom activities (93.3%), alongside a strong commitment to completing homework assignments (91.7%). These indicators reflect the course’s substantial pedagogical effectiveness and its capacity to foster learner motivation and constructive engagement. Such outcomes align with contemporary learner-centered educational paradigms that emphasize meaningful, participatory, and student-driven learning experiences. Based on these results, the study recommends a comprehensive redesign of language curricula to strengthen intrinsic motivational components and collaborative engagement. It further advocates for teacher training programs that equip educators with strategies grounded in student-centered learning principles. Moreover, it calls for the adoption of modern assessment tools focused on measuring self-engagement and cognitive regulation within second and foreign language learning contexts.